LEGAL PROTECTION FOR VICTIMS OF SEXUAL VIOLENCE IN THE UNIVERSITY ENVIRONMENT (NATIONAL CRIMINAL LAW AND ISLAMIC LAW) - Aksin, Nur; Istiqomah, Istiqomah (Jurnal Meta-Yuridis, 2026)
This study discusses legal protection for victims of sexual violence in higher education based on National Criminal Law and Islamic Law. In the National Criminal Law, victim protection is regulated in detail in Permendikbudristek Number 30 of 2021, specifically Articles 10 to 19, which regulate assistance, protection, victim recovery, and the imposition of administrative sanctions. Criminal sanctions for perpetrators are also regulated in Articles 289 to 296 of the Criminal Code. From the perspective of Islamic Law, victim protection is based on the principle of justice and respect for human dignity by applying hudud and ta'zir laws according to the level of the perpetrator's guilt, although it has not been specifically regulated in national legislation. The synergy between the provisions of Islamic Law and National Criminal Law is expected to provide comprehensive protection and encourage effective and just law enforcement for victims of sexual violence in higher education environments.